0
DUALITY
Duality Theory <ul><li>Every LP problem (called the ‘Primal’) has associated with another problem called the ‘Dual’. </li>...
Rules for converting Primal to Dual <ul><li>If the Primal is to maximize, the dual is to minimize. </li></ul><ul><li>If th...
Dual Problem Primal LP  : Max  z = c 1 x 1  + c 2 x 2  + ... + c n x n subject to: a 11 x 1  + a 12 x 2  + ... + a 1n x n ...
Example Primal Max. Z = 3x 1 +5x 2 Subject to constraints: x 1  <  4  y 1 2x 2  <  12  y 2 3x 1 +2x 2  <  18  y 3 x 1 , x ...
Example Primal Min.. Z = 10x 1 +15x 2 Subject to constraints: 5x 1  +  7x 2  >  80  6x 1  + 11x 2  >  100  x 1 , x 2  >  0
Solution Dual Max.. Z’ = 80y 1 +100y 2 Subject to constraints: 5y 1  +  6y 2  <  10  7y 1  + 11y 2  <  15  y 1 , y 2  >  0
Example Primal Max. Z = 12x 1 + 4x 2 Subject to constraints: 4x 1  + 7x 2  <   56  2x 1  + 5x 2  >  20  5x 1  +  4x 2  = 4...
Solution <ul><li>The equality constraint  5x 1  +  4x 2  = 40   can be replaced by the following two inequality constraint...
Cont… The primal problem can now take the following standard form: Max. Z = 12x 1 + 4x 2 Subject to constraints: 4x 1  + 7...
Cont… Min. Z’ = 56y 1  -20y 2  + 40y 3  – 40y 4 Subject to constraints: 4y 1  – 2y 2  +  5y 3  – 5y 4   >  12  7y 1  - 5y ...
Example Primal Min.. Z = 2x 2  + 5x 3 Subject to constraints: x 1  + x 2  >  2  2x 1  + x 2  +6x 3  <  6  x 1  - x 2  +3x ...
Solution Primal in standard form  : Max.. Z = -2x 2  - 5x 3 Subject to constraints: -x 1  - x 2  <   -2  2x 1  + x 2  +6x ...
Cont… Dual Min. Z’ = -2y 1  + 6y 2  + 4y 3  – 4y 4 Subject to constraints: -y 1  + 2y 2  + y 3  – y 4   >  0  -y 1  + y 2 ...
DUAL SIMPLEX METHOD
Introduction Suppose a “basic solution” satisfies the optimality condition but not feasible, then we apply dual simplex me...
Dual Simplex Method <ul><li>To start the dual Simplex method, the following two conditions are to be met: </li></ul><ul><l...
Example Min. Z = 3x 1  + 2x 2 Subject to constraints: 3x 1  + x 2  >  3 4x 1  + 3x 2  >  6 x 1  + x 2  <  3 x 1 , x 2  >  0
Cont… Step I: The first two inequalities are multiplied by –1 to convert them to  <  constraints and convert the objective...
Cont… Let S 1 , S 2  , S 3  be three slack variables Model can rewritten as: Z’ + 3x 1  + 2x 2  = 0 -3x 1  - x 2  +S 1  = ...
Cont… <ul><li>Initial Basic Solution is Optimal (as the optimality condition is satisfied) but infeasible.  </li></ul><ul>...
Cont… Therefore, S 1  is the departing variable and x 1  is the entering variable.  - 2 - - 1/5 -  Ratio 1 1 1/3 0 0 -1/3 ...
Cont… Optimal Solution is :  x 1 = 3/5, x 2 = 6/5, Z= 21/5 6/5 1 2/5 -1/5 0 0 0 S 3 6/5 0 -3/5 4/5 1 0 0 x 2 3/5 0 1/5 -3/...
Example Max. Z = -x 1  - x 2 Subject to constraints: x 1  + x 2  <  8 x 2  >  3 -x 1  + x 2  <  2 x 1 , x 2  >  0
Cont… Let S 1 , S 2  , S 3  be three slack variables Model can rewritten as: Z  + x 1  + x 2  = 0 x 1  + x 2  + S 1  =  8 ...
Cont… Therefore, S 2  is the departing variable and x 2  is the entering variable.  - - - 1 - -  Ratio 2 1 0 0 1 -1 0 S 3 ...
Cont… Therefore, S 3  is the departing variable and x 1  is the entering variable.  - - - - 1 -  Ratio -1 1 1 0 0 -1 0 S 3...
Cont… Optimal Solution is :  x 1 = 1, x 2 = 3, Z= -4 1 -1 -1 0 0 1 0 x 1 3 0 -1 0 1 0 0 x 2 4 0 2 1 0 0 0 S 1 -4 1 2 0 0 0...
Upcoming SlideShare
Loading in...5
×

Duality

11,209

Published on

Published in: Spiritual, Technology
0 Comments
5 Likes
Statistics
Notes
  • Be the first to comment

No Downloads
Views
Total Views
11,209
On Slideshare
0
From Embeds
0
Number of Embeds
0
Actions
Shares
0
Downloads
582
Comments
0
Likes
5
Embeds 0
No embeds

No notes for slide

Transcript of "Duality"

  1. 1. DUALITY
  2. 2. Duality Theory <ul><li>Every LP problem (called the ‘Primal’) has associated with another problem called the ‘Dual’. </li></ul><ul><li>The ‘Dual’ problem is an LP defined directly and systematically from the original (or Primal) LP model. </li></ul><ul><li>The optimal solution of one problem yields the optimal solution to the other. </li></ul><ul><li>Duality ease the calculations for the problems, whose number of variables is large. </li></ul>
  3. 3. Rules for converting Primal to Dual <ul><li>If the Primal is to maximize, the dual is to minimize. </li></ul><ul><li>If the Primal is to minimize, the dual is to maximize. </li></ul><ul><li>For every constraint in the primal, there is a dual variable. </li></ul><ul><li>For every variable in the primal, there is a constraint in the dual. </li></ul>
  4. 4. Dual Problem Primal LP : Max z = c 1 x 1 + c 2 x 2 + ... + c n x n subject to: a 11 x 1 + a 12 x 2 + ... + a 1n x n ≤ b 1 a 21 x 1 + a 22 x 2 + ... + a 2n x n ≤ b 2 : a m1 x 1 + a m2 x 2 + ... + a mn x n ≤ b m x 1 ≥ 0, x 2 ≥ 0,…….x j ≥ 0,……., x n ≥ 0. Associated Dual LP : Min. z = b 1 y 1 + b 2 y 2 + ... + b m y m subject to: a 11 y 1 + a 21 y 2 + ... + a m1 y m ≥ c 1 a 12 y 1 + a 22 y 2 + ... + a m2 y m ≥ c 2 : a 1n y 1 + a 2n y 2 + ... + a mn y m ≥ c n y 1 ≥ 0, y 2 ≥ 0,…….y j ≥ 0,……., y m ≥ 0.
  5. 5. Example Primal Max. Z = 3x 1 +5x 2 Subject to constraints: x 1 < 4 y 1 2x 2 < 12 y 2 3x 1 +2x 2 < 18 y 3 x 1 , x 2 > 0 The Primal has: 2 variables and 3 constraints. So the Dual has: 3 variables and 2 constraints Dual Min. Z’ = 4y 1 +12y 2 +18y 3 Subject to constraints: y 1 + 3y 3 > 3 2y 2 +2y 3 > 5 y 1 , y 2 , y 3 > 0 We define one dual variable for each primal constraint.
  6. 6. Example Primal Min.. Z = 10x 1 +15x 2 Subject to constraints: 5x 1 + 7x 2 > 80 6x 1 + 11x 2 > 100 x 1 , x 2 > 0
  7. 7. Solution Dual Max.. Z’ = 80y 1 +100y 2 Subject to constraints: 5y 1 + 6y 2 < 10 7y 1 + 11y 2 < 15 y 1 , y 2 > 0
  8. 8. Example Primal Max. Z = 12x 1 + 4x 2 Subject to constraints: 4x 1 + 7x 2 < 56 2x 1 + 5x 2 > 20 5x 1 + 4x 2 = 40 x 1 , x 2 > 0
  9. 9. Solution <ul><li>The equality constraint 5x 1 + 4x 2 = 40 can be replaced by the following two inequality constraints: </li></ul><ul><li>5x 1 + 4x 2 < 40 </li></ul><ul><li>5x 1 + 4x 2 > 40 -5x 1 - 4x 2 < -40 </li></ul><ul><li>The second inequality 2x 1 + 5x 2 > 20 can be changed to the less-than-or-equal-to type by multiplying both sides of the inequality by -1 and reversing the direction of the inequality; that is, </li></ul><ul><li>-2x 1 - 5x 2 < -20 </li></ul>
  10. 10. Cont… The primal problem can now take the following standard form: Max. Z = 12x 1 + 4x 2 Subject to constraints: 4x 1 + 7x 2 < 56 -2x 1 - 5x 2 < -20 5x 1 + 4x 2 < 40 -5x 1 - 4x 2 < -40 x 1 , x 2 > 0
  11. 11. Cont… Min. Z’ = 56y 1 -20y 2 + 40y 3 – 40y 4 Subject to constraints: 4y 1 – 2y 2 + 5y 3 – 5y 4 > 12 7y 1 - 5y 2 + 4y 3 – 4y 4 > 4 y 1 , y 2 , y 3 , y 4 > 0 The dual of this problem can now be obtained as follows:
  12. 12. Example Primal Min.. Z = 2x 2 + 5x 3 Subject to constraints: x 1 + x 2 > 2 2x 1 + x 2 +6x 3 < 6 x 1 - x 2 +3x 3 = 4 x 1 , x 2 , x 3 > 0
  13. 13. Solution Primal in standard form : Max.. Z = -2x 2 - 5x 3 Subject to constraints: -x 1 - x 2 < -2 2x 1 + x 2 +6x 3 < 6 x 1 - x 2 +3x 3 < 4 - x 1 + x 2 - 3x 3 < -4 x 1 , x 2 , x 3 > 0
  14. 14. Cont… Dual Min. Z’ = -2y 1 + 6y 2 + 4y 3 – 4y 4 Subject to constraints: -y 1 + 2y 2 + y 3 – y 4 > 0 -y 1 + y 2 - y 3 + y 4 > -2 6y 2 + 3y 3 - 3y 4 > -5 y 1 , y 2 , y 3 , y 4 > 0
  15. 15. DUAL SIMPLEX METHOD
  16. 16. Introduction Suppose a “basic solution” satisfies the optimality condition but not feasible, then we apply dual simplex method. In regular Simplex method, we start with a Basic Feasible solution (which is not optimal) and move towards optimality always retaining feasibility. In the dual simplex method, the exact opposite occurs. We start with a “optimal” solution (which is not feasible) and move towards feasibility always retaining optimality condition.The algorithm ends once we obtain feasibility.
  17. 17. Dual Simplex Method <ul><li>To start the dual Simplex method, the following two conditions are to be met: </li></ul><ul><li>The objective function must satisfy the optimality conditions of the regular Simplex method. </li></ul><ul><li>All the constraints must be of the type  . </li></ul>
  18. 18. Example Min. Z = 3x 1 + 2x 2 Subject to constraints: 3x 1 + x 2 > 3 4x 1 + 3x 2 > 6 x 1 + x 2 < 3 x 1 , x 2 > 0
  19. 19. Cont… Step I: The first two inequalities are multiplied by –1 to convert them to < constraints and convert the objective function into maximization function. Max. Z’ = -3x 1 - 2x 2 where Z’= -Z Subject to constraints: -3x 1 - x 2 < -3 -4x 1 - 3x 2 < -6 x 1 + x 2 < 3 x 1 , x 2 > 0
  20. 20. Cont… Let S 1 , S 2 , S 3 be three slack variables Model can rewritten as: Z’ + 3x 1 + 2x 2 = 0 -3x 1 - x 2 +S 1 = -3 -4x 1 - 3x 2 +S 2 = -6 x 1 + x 2 +S 3 = 3 Initial BS is : x 1 = 0, x 2 = 0, S 1 = -3, S 2 = -6, S 3 = 3 and Z=0.
  21. 21. Cont… <ul><li>Initial Basic Solution is Optimal (as the optimality condition is satisfied) but infeasible. </li></ul><ul><li>Choose the most negative basic variable. Therefore, S 2 is the departing variable. </li></ul><ul><li>Calculate Ratio = |Z row / S 2 row| (S 2 < 0) </li></ul><ul><li>Choose minimum ratio. Therefore, x 2 is the entering variable. </li></ul>- - - 2/3 3/4 - Ratio 3 1 0 0 1 1 0 S 3 -6 0 1 0 -3 -4 0 S 2 -3 0 0 1 -1 -3 0 S 1 0 0 0 0 2 3 1 Z Sol. S 3 S 2 S 1 x 2 x 1 Z Coefficients of: Basic Variable
  22. 22. Cont… Therefore, S 1 is the departing variable and x 1 is the entering variable. - 2 - - 1/5 - Ratio 1 1 1/3 0 0 -1/3 0 S 3 2 0 -1/3 0 1 4/3 0 x 2 -1 0 -1/3 1 0 -5/3 0 S 1 4 0 2/3 0 0 1/3 1 Z Sol. S 3 S 2 S 1 x 2 x 1 Z Coefficients of: Basic Variable
  23. 23. Cont… Optimal Solution is : x 1 = 3/5, x 2 = 6/5, Z= 21/5 6/5 1 2/5 -1/5 0 0 0 S 3 6/5 0 -3/5 4/5 1 0 0 x 2 3/5 0 1/5 -3/5 0 1 0 x 1 21/5 0 3/5 1/5 0 0 1 Z Sol. S 3 S 2 S 1 x 2 x 1 Z Coefficients of: Basic Variable
  24. 24. Example Max. Z = -x 1 - x 2 Subject to constraints: x 1 + x 2 < 8 x 2 > 3 -x 1 + x 2 < 2 x 1 , x 2 > 0
  25. 25. Cont… Let S 1 , S 2 , S 3 be three slack variables Model can rewritten as: Z + x 1 + x 2 = 0 x 1 + x 2 + S 1 = 8 -x 2 + S 2 = -3 -x 1 + x 2 + S 3 = 2 x 1 , x 2 > 0 Initial BS is : x 1 = 0, x 2 = 0, S 1 = 8, S 2 = -3, S 3 = 2 and Z=0.
  26. 26. Cont… Therefore, S 2 is the departing variable and x 2 is the entering variable. - - - 1 - - Ratio 2 1 0 0 1 -1 0 S 3 -3 0 1 0 -1 0 0 S 2 8 0 0 1 1 1 0 S 1 0 0 0 0 1 1 1 Z Sol. S 3 S 2 S 1 x 2 x 1 Z Coefficients of: Basic Variable
  27. 27. Cont… Therefore, S 3 is the departing variable and x 1 is the entering variable. - - - - 1 - Ratio -1 1 1 0 0 -1 0 S 3 3 0 -1 0 1 0 0 x 2 5 0 1 1 0 1 0 S 1 -3 0 1 0 0 1 1 Z Sol. S 3 S 2 S 1 x 2 x 1 Z Coefficients of: Basic Variable
  28. 28. Cont… Optimal Solution is : x 1 = 1, x 2 = 3, Z= -4 1 -1 -1 0 0 1 0 x 1 3 0 -1 0 1 0 0 x 2 4 0 2 1 0 0 0 S 1 -4 1 2 0 0 0 1 Z Sol. S 3 S 2 S 1 x 2 x 1 Z Coefficients of: Basic Variable
  1. A particular slide catching your eye?

    Clipping is a handy way to collect important slides you want to go back to later.

×